AI IN BUSINESS EDUCATION: ISSUES AND CHALLENGES - Sharma, Lovely (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Inadequate techniques for teaching artificial intelligence abound in business curricula. Mechanized, rule-based systems can easily reinforce negative stereotypes of business and business people as superficial and irrelevant. This paper surveys other AI systems, and in doing so, addresses several key business education-associated issues. Notably, we emphasize the need for business educators to consider how to prepare their students to profitably interact with these systems in professional environments. Issues concerning personal, professional, and pedagogical development are also discussed, as are a number of indispensable contributions the humanities disciplines could make in these areas. Several challenges are noted and suggestions provided t aid the development of business education courses designed to inform and/or foster general, critical, and ethical AI literacy. As many business leaders and business students are new to the subject of artificial intelligence, or have limited knowledge of it, the job of the business educator is to make the subject relevant and interesting and to provide students with skills they can use in their careers. To begin, business instructors need to be aware of the AI systems that exist, in order to be capable of explaining how they have the potential to benefit a firm, an industry, or the global economy. Furthermore, business faculty need to provide an academic setting in which all students can profitably interact with AI technologies. In particular, business students should be prepared to deal with any conceivable AI topic in any professional setting. Although a business curriculum that attempts to accomplish this might encompass students studying subjects other than AI, the knowledge gained by students so engaged can be used in far more situations than just those relating specifically to AI. Throughout, the focus should be on graduates being able to design and use these systems, with particular emphasis on the ethical and job displacement dimensions of bringing AI into the workplace.